Girls in the juvenile justice system: leave no girl's health un-addressed. - Guthrie, Barbara J; Hoey, Erin; Ravoira, LaWanda; Kintner, Eileen (Journal of pediatric nursing, 2002)
Despite an increase in middle to older aged adolescent females' early contact with the juvenile justice system, inadequate health care remains a concern. This descriptive study surveyed the physical and mental health needs of 130 self-selected, nonrandomized girls aged 12 to 18 years, with a mean age of 15.42 years (SD, 1.24), who were involved with a juvenile justice diversional program located in a southeastern region of the United States. Findings revealed early initiation of sexual-related activities (mean age, 13.9 years; SD, 1.49) and substance use (mean age, 12.9 years; SD, 1.53). The data suggest an increasing need for pediatric nurses, and in particular advanced practice nurses, to provide gender-responsive health care and health promotion services to early middle-childhood females in the juvenile justice system.
Keywords: Adolescent; Adolescent Behavior; Alcoholism; Child; Child Welfare; Cross-Sectional Studies; Female; Health Promotion; Humans; Juvenile Delinquency; Needs Assessment; Nurse's Role; Pediatric Nursing; Preventive Health Services; Sampling Studies; Sexual Behavior; Substance-Related Disorders; United States